1996
DOI: 10.1128/jvi.70.11.7921-7928.1996
|View full text |Cite
|
Sign up to set email alerts
|

DNA immunization confers protection against murine cytomegalovirus infection

Abstract: The murine cytomegalovirus (MCMV) immediate-early gene 1 (IE1) encodes an 89-kDa phosphoprotein (pp89) which plays a key role in protecting BALB/c mice against the lethal effects of the MCMV infection. In this report, we have addressed the question of whether "naked DNA" vaccination with a eukaryotic expression vector (pcDNA-89) that contains the MCMV IE1 gene driven by a strong enhancer/promoter can confer protection. BALB/c mice were immunized intradermally with pcDNA-89 or with the plasmid backbone pcDNAI/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(14 citation statements)
references
References 44 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…These early studies had several important features: they showed that DNA vaccines could induce immunity in several different disease models; that antibody, Th, and CTL responses could all be generated; that a response could be induced by different routes of immunization (e.g., intramuscular, epidermal, or mucosal); and, in the case of influenza, that these vaccines could protect animals from subsequent challenge with pathogenic virus. Since then, genetic immunization has been investigated in numerous infectious disease models in addition to those mentioned above, with vaccines currently in various stages of development for HIV-2 (7,8), herpes simplex virus 1 (HSV-1) (9), HSV-2 (10), rabies (11), hepatitis C (12), tuberculosis (13), malaria (14), mycoplasma (15), Leishmania major (16), cytomegalovirus (17), Toxoplasma gondii (18), rotavirus (19), and, most recently, Ebola (20). In addition to infectious diseases applications, genetic immunization may have potential as a means of cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…These early studies had several important features: they showed that DNA vaccines could induce immunity in several different disease models; that antibody, Th, and CTL responses could all be generated; that a response could be induced by different routes of immunization (e.g., intramuscular, epidermal, or mucosal); and, in the case of influenza, that these vaccines could protect animals from subsequent challenge with pathogenic virus. Since then, genetic immunization has been investigated in numerous infectious disease models in addition to those mentioned above, with vaccines currently in various stages of development for HIV-2 (7,8), herpes simplex virus 1 (HSV-1) (9), HSV-2 (10), rabies (11), hepatitis C (12), tuberculosis (13), malaria (14), mycoplasma (15), Leishmania major (16), cytomegalovirus (17), Toxoplasma gondii (18), rotavirus (19), and, most recently, Ebola (20). In addition to infectious diseases applications, genetic immunization may have potential as a means of cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Acute MCMV infection by IP injection leads to a peak viral burden in spleen at 3-6 days, and in salivary gland at 10-14 days (11). After 1 month, mice have recovered from the acute phase of the infection, and have low MCMV titers in the salivary gland and other organs (11,30). In previous studies, we have demonstrated that mice develop persistent MCMV infection after recovery from the acute infection (13,32,39).…”
Section: Peptide-specific Immune Responses During Chronic MCMV Infectionmentioning
confidence: 88%
“…Mice with chronic MCMV infection had consistent immune responses to the peptide YPHFMPTNL as measured by IFN-γ ELISPOT. Acute MCMV infection by IP injection leads to a peak viral burden in spleen at 3-6 days, and in salivary gland at 10-14 days (11). After 1 month, mice have recovered from the acute phase of the infection, and have low MCMV titers in the salivary gland and other organs (11,30).…”
Section: Peptide-specific Immune Responses During Chronic MCMV Infectionmentioning
confidence: 99%
See 2 more Smart Citations